Thoughts on Ferguson - Pond, Gina A., Rev. (Open Source Alexandrian, 2014)
Opening this podcast with a passage from “The Prophet” by Kahlil Gibran, Rev. Pond, using the Ferguson Uprising as a jumping off point, discusses the prejudices in our society and how we really are all the same. She states how there seems to be a continued series of violent acts among our neighbors. She hopes through awareness of these incidents that it will be the catalyst for change.
The Heretic Speaks episode 5, August 20, 2014
heretic-speaks_ep05_20140820.mp3 | MP3 Format Sound | 00:17:22 | 23.85 MB | 11/28/2018 10:34:16 AM | .mp3 |
Keywords: Pond, Gina, 1976-; Discrimination in criminal justice administration; Ferguson (Mo.); Police Department; Civil rights; Good and evil; Prejudices; Podcasts